If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6x-87=2x-11
We move all terms to the left:
6x-87-(2x-11)=0
We get rid of parentheses
6x-2x+11-87=0
We add all the numbers together, and all the variables
4x-76=0
We move all terms containing x to the left, all other terms to the right
4x=76
x=76/4
x=19
| -2x+5x-9=3(x-6)-3 | | 5t^2+3t+2=5 | | 12w−10w=12 | | 1-4x-5=x | | c-8=25 | | 8(14x-15)=-72 | | x*x-8x=24 | | -13p-6(6-4p)=6(p-3)-28 | | 6x+25=-30x+25 | | 4(-8x+12)=3x+24-x | | d+9=25 | | 9x-(5x+8)=3x+7 | | 5a^2=-12a+15 | | 28(c-62)=26,600 | | (3x-5)=(6x-14) | | 150m-75m+54625=55000-200m | | 9x-40=122 | | -2x+-3=-2x+4 | | 0.5x−4=0.18x+4 | | -.5x+6x+2=20 | | 21x^2-4x+6=7 | | 5(×+1)=21+3x | | -2(x-3)=5(x+11) | | 5f+2.50=27.50 | | 13x+12=6x+33 | | -2/3(m-3)=21/5 | | 3a-1=28 | | 20b=-340 | | 11k^2-9k-4=-5 | | 2.1/10n=1.1/6 | | 6+n/5=-3 | | 9x-15=8x+12 |